2014
DOI: 10.5213/inj.2014.18.3.155
|View full text |Cite
|
Sign up to set email alerts
|

The Study About Physical Activity for Subjects With Prevention of Benign Prostate Hyperplasia

Abstract: PurposeThe number of benign prostatic hyperplasia (BPH) subjects has been increasing worldwide, and many studies have been conducted to determine the treatment that can delay drug therapy or surgery. Subsequently, most of these studies involved physical activity (PA) and associated factors. Therefore, we aimed to determine factors associated with BPH prevalence based on a review of past and present studies and to investigate the effect of a healthy lifestyle as a protective factor of BPH occurrence.MethodsWe s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 23 publications
1
13
0
3
Order By: Relevance
“…In addition, studies have identified several risk factors associated with an increased risk of BPH, including cardiovascular risk factors, a prior history of STDs (especially gonorrhoea), metabolic syndrome, chronic inflammation and sedentary activity [10,15,13,29,30]. HIV-infected men are at a higher risk of contracting STDs, which could be expected to translate into an increased risk of BPH [17,19,31].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have identified several risk factors associated with an increased risk of BPH, including cardiovascular risk factors, a prior history of STDs (especially gonorrhoea), metabolic syndrome, chronic inflammation and sedentary activity [10,15,13,29,30]. HIV-infected men are at a higher risk of contracting STDs, which could be expected to translate into an increased risk of BPH [17,19,31].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis, containing 19 studies, reports a positive association between Body Mass Index (BMI) and Lower urinary tract syndrome (LUTS) related to BPH (odds ratio (OR) = 1.28%) (Wang, Mao et al 2012). Many investigations have shown that obese men have a higher risk of BPH (Wang, Hsieh et al 2011, Corona, Vignozzi et al 2014 and proved that the impact on male aging can be halted by aerobic exercise (Brown and Emberton 2009, Poon and McVary 2009, Jung, Lee et al 2012, Lee, Kim et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Benign prostatic hyperplasia (BPH) is common among older men, with 612 million cases predicted to occur by 2018 1, 2. Histologically, BPH is defined as the presence of stromal‐glandular hyperplasia within the prostate gland 3.…”
Section: Introductionmentioning
confidence: 99%
“…Benign prostatic hyperplasia (BPH) is common among older men, with 612 million cases predicted to occur by 2018. 1,2 Histologically, BPH is defined as the presence of stromal-glandular hyperplasia within the prostate gland. 3 Many patients with BPH present with bothersome lower urinary tract symptoms (LUTS), typically an increase in urinary urgency and frequency, nocturia, decreased and intermittent force of stream and a sense of incomplete bladder emptying 3 ; these symptoms can have a substantial negative impact on quality of life (QoL).…”
Section: Introductionmentioning
confidence: 99%